Використання алгоритму рою часток для оптимізації організаційних моделей взаємодії учасників будівельного ринку - Шпаков, А. В. (Ways to Improve Construction Efficiency, 2012)
It is proposed to use the classic particle swarm algorithm and its modifications for use in organizational modeling of Ukraine competitive construction industry environment and its individual segments, including the study of new organizational forms of construction companies such as "network" organizations or company created on the network principle.